2016
DOI: 10.1016/j.apsb.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide sulfonate ameliorates lipopolysaccharide-induced acute lung injury in mice by down-regulating MAPK and NF-κB pathways

Abstract: Acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) is a severe, life-threatening medical condition characterized by widespread inflammation in the lungs, and is a significant source of morbidity and mortality in the patient population. New therapies for the treatment of ALI are desperately needed. In the present study, we examined the effect of andrographolide sulfonate, a water-soluble form of andrographolide (trade name: Xi-Yan-Ping Injection), on lipopolysaccharide (LPS)-induced ALI and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…The levels of Ifn-γ, GzmB, Prf and FasL mRNAs were analyzed by qRT-PCR. Total RNA was isolated using TriZol reagent (Invitrogen), and cDNA was synthesized using the PrimeScript RT reagent kits (Takara) according to the manufacturers׳ instructions as previous reported 27 . The qRT-PCR was performed with SYBR Premix Ex Taq TM (Takara) and CFX96 Real-time system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…The levels of Ifn-γ, GzmB, Prf and FasL mRNAs were analyzed by qRT-PCR. Total RNA was isolated using TriZol reagent (Invitrogen), and cDNA was synthesized using the PrimeScript RT reagent kits (Takara) according to the manufacturers׳ instructions as previous reported 27 . The qRT-PCR was performed with SYBR Premix Ex Taq TM (Takara) and CFX96 Real-time system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Another study reported that the iNOS gene is a highly inducible gene and its transcription is readily upregulated by inflammatory cytokines (Nassi et al 2016). Excess cytokines production might be caused by the LPS ability to stimulate mitogen activated protein kinase (MAPK) (Peng et al 2016) and NF-κB (Jang et al 2017) pathways. This is compatible with the LPS induced increase in serum IL-6 level in the present study which is also in agreement with Liu and Cheng (2016) and Weifeng et al (2016).…”
Section: Immunohistochemical Assessment Of Inosmentioning
confidence: 99%
“…Previous studies showed that inflammatory injuries trigger a robust influx of neutrophils and monocytes to the site of tissue injury (7) and the damaged or dead cells are thought to trigger the inflammasome-dependent responses, then alert the innate immune system to the impending tissue damage (8). Previous studies confirmed that the mechanism of some drugs, including Decitabine, 5-azacitidine, Losartan and Andrographolide sulfonate, protect lungs against injury induced by sepsis via the inhibition of the phosphorylation of the ERK, JNK and p38 MAPK, which may result in the suppression of the proinflammatory cytokine expression (16,17,21). Inhibition of the p38 MAPK and JNK, but not ERK could alleviate inflammatory cell infiltration and microvascular permeability in sepsis-induced ARDS mice (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined that in mice with cecal ligation and puncture (CLP) the protein expression of Toll-like receptor 4 (TLR4), phosphorylated (p)-p38, p-JNK and p-ERK was increased, whereas treatment with Compound 9a protected against septic injury by suppressing MAPK-mediated inflammatory signaling (15). In a lipopolysaccharide (LPS)-stimulated ARDS mouse model, some drugs or compounds (including Decitabine, 5-azacitidine, Andrographolide sulfonate, Hydroxy-Jolkinolide B-1 and Astilbin) alleviated LPS-induced ARDS by suppressing LPS-induced activation of the MAPK signaling pathways by blocking the phosphorylation of JNK, ERK and p38 in lung tissues (16)(17)(18)(19). Previous studies indicated that glycyrrhizic acid and Losartan have a protective effect against sepsis-induced acute lung injury by inhibiting the inflammatory response, reducing damage from oxidative stress, and apoptosis via inactivation of JNK and p38 MAPK (20,21).…”
Section: Modulation Of Mitogen-activated Protein Kinase Attenuates Sementioning
confidence: 99%